PERAN SATUAN POLISI PAMONG PRAJA DALAM PENERTIBAN PEDAGANG KAKI LIMA DI KABUPATEN BULUKUMBA - Irfan Z, Muh; Mahsyar, Abdul; Ma'ruf, Adnan (Universitas Muhammadiyah Makassar, 2025)
This study aims to determine the role of the Bulukumba Regency Civil Service Police Unit in controlling street vendors in Bulukumba Regency in 2023. The type of research used in this study is qualitative and the type of research used is descriptive, where the type and type of research explain in detail how the role of Satpol PP in controlling street vendors in Bulukumba Regency. The results of the study revealed the role of the Bulukumba Regency Civil Service Police Unit as a regulatory role, its advantages include: the implementation of tasks has followed the applicable Standard Operating Procedures.